KEBUTUHAN GURU SEKOLAH DASAR INKLUSI DALAM MENINGKATKAN KOMPETENSI MELALUI MEDIA VIDEO - Edi Purnomo (Balai Besar Guru Penggerak Jawa Timur, 2016)
This study is a research of instructional video development which aims to gain informations about the needs of inclusive primary school teachers in improving their competencies through video media. Such information includes: implementation constraints, teacher characteristics, teacher attitudes, and competencies required of teachers. The study used a survey research design. The data collection with a focus group discussion (FGD) and the enclosed questionnaire. The results showed that the main obstacle implementation of inclusive education is the classroom teacher competence is still not good and the number of special guidance counselor (GPK) is still lacking. The majority of primary school inclusion teacher educational background S1PGSD and no experience teaching in inclusive schools. Many theachers of inclusion primary school have not attended training on inclusive education. The efforts to increase the competence of self-done by discussing with fellow-teachers. The attitude of teachers to implement inclusive education is very good but the handling of learning obstacles still lacking. Teachers need to increase the competence of inclusive learning strategy. The study concluded that primary school inclusion teachers need a tutorial learning strategies in the classroom inclusion. The packed tutorial in the videos media so that it can individually study or the training delivered. AbstrakPenelitian ini merupakan tahapan penelitian pengembangan media video yang bertujuan menggali informasi kebutuhan guru sekolah dasar inklusi dalam meningkatkan kompetensi melalui media video. Informasi tersebut meliputi: kendala pelaksanaan, karakteristik guru, sikap guru, dan kompetensi yang dibutuhkan guru. Penelitian menggunakan desain penelitian survey. Pengumpulan data dengan focus group discussion (FGD) dan kuesioner tertutup. Hasil penelitianmenunjukkan bahwa kendala utama penyelenggaraan pendidikan inklusif adalah kompetensi guru kelas masih kurang baik dan jumlah guru pembimbing khusus (GPK) masih kurang. Guru SD inklusi mayoritas berlatar belakang pendidikan S1 PGSD dan belum berpengalaman mengajar di sekolah inklusi. Banyak Guru SD inklusi yang belum mengikuti pelatihan pendidikan inklusif. Upaya untuk meningkatkan kompetensi diri dilakukan dengan berdiskusi dengan sesama guru. Sikap guru terhadap pelaksanaan pendidikan inklusif sangat baik, tetapi dalam menangani kendala pembelajaran masih kurang. Guru membutuhkan peningkatan kompetensi tentang strategi pembelajaran inklusif. Penelitian ini menyimpulkan bahwa guru SD inklusi membutuhkan tutorial strategi pembelajaran di kelas inklusi. Tutorial dikemas dalam media video sehingga dapat dipelajari secara mandiri maupun disampaikan dalam pelatihan.